Evolution of biomolecular loadings along a major river system. (15th February 2018) - Freymond, Chantal V.; Kündig, Nicole; Stark, Courcelle; Peterse, Francien; Buggle, Björn; Lupker, Maarten; Plötze, Michael; Blattmann, Thomas M.; Filip, Florin; Giosan, Liviu; Eglinton, Timothy I.
Abstract: Understanding the transport history and fate of organic carbon (OC) within river systems is crucial in order to constrain the dynamics and significance of land–ocean interactions as a component of the global carbon cycle. Fluvial export and burial of terrestrial OC in marine sediments influences atmospheric CO2 over a range of timescales, while river-dominated sedimentary sequences can provide valuable archives of paleoenvironmental information. While there is abundant evidence that the association of organic matter (OM) with minerals exerts an important influence on its stability as well as hydrodynamic behavior in aquatic systems, there is a paucity of information on where such associations form and how they evolve during fluvial transport. Here, we track total organic carbon (TOC) and terrestrial biomarker concentrations (plant wax-derived long-chain fatty acids (FA), branched glycerol dialkyl glycerol tetraethers (brGDGTs) and lignin-derived phenols) in sediments collected along the entire course of the Danube River system in the context of sedimentological parameters. Mineral-specific surface area-normalized biomarker and TOC concentrations show a systematic decrease from the upper to the lower Danube basin. Changes in OM loading of the available mineral phase correspond to a net decrease of 70–80% of different biomolecular components. Ranges for biomarker loadings on Danube River sediments, corresponding to 0.4–1.5 μgFA /m 2 for long-chain ( n -C24–32 ) fatty acids and 17–71 ngbrGDGT /m 2 for brGDGTs, are proposed as a benchmark for comparison with other systems. We propose that normalizing TOC as well as biomarker concentrations to mineral surface area provides valuable quantitative constraints on OM dynamics and organo-mineral interactions during fluvial transport from terrigenous source to oceanic sink.